Smart Cities Applications, Technologies, Standards, and Driving Factors - McClellan, Stan.; Jimenez, Jesus A.; Koutitas, George; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reviews the applications, technologies, standards, and other issues related to Smart Cities. The book is divided into broad topical sections including Vision & Reality, Technologies & Standards, Transportation Considerations, and Infrastructure & Environment. In these sections, authors who are experts in their fields present essential aspects of applications, technologies, requirements, and best-practices. In all cases, the authors have direct, substantive experience with the subject and present an important viewpoint driven by industry or governmental interests; the authors have each participated in the development and/or deployment of constituent technologies, standards, and applications, and share unique perspectives on key areas of the Smart City.
Introduction -- Smart Buildings -- The Energy Layer -- The Sensor/Actuator Layer -- The Middleware Layer -- The Application Layer -- Conclusion.
Keywords: Telecommunication; Electric power production; Application software; Energy policy; Energy and state; Communications Engineering, Networks; Electrical Power Engineering; Computer and Information Systems Applications; Energy Policy, Economics and Management